Experiences of parenting for autistic children in Australia and Italy: a qualitative cross-cultural comparison - Frigerio, Alessandra; Knight, Tess; Rella, Riccardo; Sinigaglia, Elena; Camussi, Elisabetta; Montali, Lorenzo (Frontiers in Psychology, 2024)
Introduction Parents vary in their gradual adaptation to the demands of caring for an autistic child. Their experiences can be positive, negative, or a combination of both, depending on the severity of the cases and various personal and social factors. Cross-cultural comparisons can aid in understanding how contextual factors, such as the availability of social and health services, and cultural factors, such as family relationships and the distribution of care burden, may influence the caregiving experience. However, there is a limited amount of cross-cultural research on this topic, which is almost exclusively quantitative. Aims and methods From an ecocultural perspective, our interview-based study aimed to explore the experiences of Australian (15) and Italian (11) parents of autistic children living in their respective countries. Results The analysis identified three main themes. Life through autism, autism through life: coexisting with an unexpected life partner, Parenting autistic children: reorganization of parents’ subjectivity and familiar dynamics, and The unseen side of disability: autism communities between inclusion and segregation. Discussion Our comparative approach reveals both commonalities and differences between the two groups of participants. The similarities support features previously identified in the literature: the emotional and physical burden on parents and the positive impact on parental identity. The differences relate to the diagnostic process, interactions with health professionals, the impact of autism on family dynamics and parental perspectives, and the role assigned to siblings. Despite facing similar challenges, these differences reveal how Italian and Australian parents articulate different understandings linked to social and cultural differences.